A Predicted Mannoprotein Participates in Cryptococcus gattii Capsular Structure - Julia Catarina Vieira Reuwsaat (American Society for Microbiology, 2018)
ABSTRACT The yeast-like pathogen Cryptococcus gattii is an etiological agent of cryptococcosis. The major cryptococcal virulence factor is the polysaccharide capsule, which is composed of glucuronoxylomannan (GXM), galactoxylomannan (GalXM), and mannoproteins (MPs). The GXM and GalXM polysaccharides have been extensively characterized; however, there is little information about the role of mannoproteins in capsule assembly and their participation in yeast pathogenicity. The present study characterized the function of a predicted mannoprotein from C. gattii, designated Krp1. Loss-of-function and gain-of-function mutants were generated, and phenotypes associated with the capsular architecture were evaluated. The null mutant cells were more sensitive to a cell wall stressor that disrupts beta-glucan synthesis. Also, these cells displayed increased GXM release to the culture supernatant than the wild-type strain did. The loss of Krp1 influenced cell-associated cryptococcal polysaccharide thickness and phagocytosis by J774.A1 macrophages in the early hours of interaction, but no difference in virulence in a murine model of cryptococcosis was observed. In addition, recombinant Krp1 was antigenic and differentially recognized by serum from an individual with cryptococcosis, but not with serum from an individual with candidiasis. Taken together, these results indicate that C. gattii Krp1 is important for the cell wall structure, thereby influencing capsule assembly, but is not essential for virulence in vivo. IMPORTANCE Cryptococcus gattii has the ability to escape from the host’s immune system through poorly understood mechanisms and can lead to the death of healthy individuals. The role of mannoproteins in C. gattii pathogenicity is not completely understood. The present work characterized a protein, Kpr1, that is essential for the maintenance of C. gattii main virulence factor, the polysaccharide capsule. Our data contribute to the understanding of the role of Kpr1 in capsule structuring, mainly by modulating the distribution of glucans in C. gattii cell wall.